2016
DOI: 10.1007/s11655-016-2611-1
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate interfere in modulation of Foxp3 expression in synovial cells in collagen-induced arthritis rats

Abstract: Artesunate could increase the expression of Foxp3 in a dose-dependent manner, and thus reduce pannus formation and erosion of cartilage and bone to prevent lesions from rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Studies ( 114 , 115 ) have found that the antimalarial drug artemisinin analog artesunate (ARS) has strong immunosuppressive activity in RA model, which can inhibit the formation of germinal centers, B cell proliferation and the production of autoantibodies, increase Foxp3 expression, reduce the formation of pannus, and cartilage and bone erosion. ARS is also an effective antioxidant ( 116 ), which is able to inhibit the production of ROS in osteoclast precursor cells and maintain oxidative homeostasis, thereby inhibiting osteoclastogenesis, by activating p62/Nrf2 signaling pathway and inhibiting NFATc1 signaling.…”
Section: Terpenoidsmentioning
confidence: 99%
“…Studies ( 114 , 115 ) have found that the antimalarial drug artemisinin analog artesunate (ARS) has strong immunosuppressive activity in RA model, which can inhibit the formation of germinal centers, B cell proliferation and the production of autoantibodies, increase Foxp3 expression, reduce the formation of pannus, and cartilage and bone erosion. ARS is also an effective antioxidant ( 116 ), which is able to inhibit the production of ROS in osteoclast precursor cells and maintain oxidative homeostasis, thereby inhibiting osteoclastogenesis, by activating p62/Nrf2 signaling pathway and inhibiting NFATc1 signaling.…”
Section: Terpenoidsmentioning
confidence: 99%
“…To establish the CIA model, Wistar rats (male, 9 weeks) were immunized intradermally at the base of the tail with bovine type II collagen (CII) emulsified in Freund's adjuvant on Day 0 and Day 7, as previously described [36]. CIA rats were randomly chosen to receive an intraarticular injection of 2*10 8 PFU of Ad-shRNA-SMOC2 (n = 5) or the control shRNA vector (n = 5) in each ankle on Day 14 and Day 21.…”
Section: Rna Stabilitymentioning
confidence: 99%
“…40,41 The majority of experimental data have been raised in animal models of rheumatoid arthritis with wellestablished models such as type II collagen-induced arthritis (CIA) or Freud's complete adjuvant (FCA)-induced arthritis in mice or rats (Table 1). [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Some authors also applied experimental in vitro settings by using lipopolysaccharide (LPS)-stimulated murine macrophages or fibroblast-like synoviocytes isolated from rheumatoid arthritis patients. 16,21 Synovial tissue biopsies from rheumatoid patients also have been investigated.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Symptomatic improvements of the disease were decreased joint and food pad inflammation and swelling, decreased pannus formation, reduced cartilage and bone erosion, reduced paw edema as well as improved functional parameters (stair climbing ability, motility, suppression of mechanical allodynia) and improved clarity of articular cavity (Table 1). [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] At the microscopic level, reduced proliferation of fibrous connective tissue, chondrocytes, and blood capillaries 1). Tfh cells aggravate antibody-mediated autoimmune reactions.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%